Evaluation of the rice germplasm disease incidence in upland and periodically flooded lowland in Amazonas, Brazil. - Menezes dos Santos, Jorge Roland; Galvão, Expedito Ubirajara Peixoto (Pesquisa Agropecuaria Brasileira, 2014)
The main rice diseases that occurre in Manaus, AM, Brazil, were evaluated by two experiments. On of them was placed on the upland, and the other one on the periodically flooded lowland. This paper also reports the occurrence of Pyricularia oryzae, Helminthosporium oryzae, Rhynchosporium oryzae, Cercospora oryzae and Rhizoctonia solani attacking rice in the Amazonas state. Grain spot and leaf spot caused by H. oryzae were the principal problems on the upland. On the lowland, the incidence of R. solani was high, more than 25%, but, the attack was late and the grain production was not affected.